A classical vascular dilemma: Limb salvage or amputation? - (:unkn) unknown (My University, 2001)
Popliteal artery injuries are the most challenging of all extremity vascular injuries. The popliteal vein, infrapopliteal arteries and the tibial nerve are the most commonly injured structures in penetrating popliteal trauma patients. Despite the experience obtained from the major wars in this century, ongoing advances in vascular surgery and near 100% limb salvage reports from current literature in popliteal artery penetrating trauma, there is still an ongoing debate about the management of such injuries. These injuries require a multidisciplinary approach for appropriate management. One of the major conflicts is the decision between amputation or salvaging the limb. According to the current data and our clinical experience, evaluation and decision making in this group of injuries is mostly patient dependent. In this case report, we present a young man with a left popliteal region gunshot injury. Immediately after the injury a limb salvage procedure was performed by our team. Now the patient has a conserved limb but functionally amputated extremity after 4 months of hospital stay.
Keywords: Gunshot wounds; Penetrating vascular injury; Treatment